Chapter Realizzazione di un video a 360°: dimensioni tecniche e operative - Luzzi, Damiana (Studi e saggi, 2022)
After a brief overview of some sectors where 360° video is used and which can benefit from its adoption, the chapter illustrates the technical aspects of 360 ° video, the equipment needed for shooting, the requirements and functionalities to choose the most suitable 360 ​​° camera, the shooting strategies, the delivery methods, the software for inserting interaction points, concepts such as immersion, presence and degrees of freedom, and the technical terms that must be known in order to easily move in the production of 360 ​​° video.